Imprinted gene alterations in the kidneys of growth restricted offspring may be mediated by a long non-coding RNA - Thu N. A. Doan; James M. Cowley; Aaron L. Phillips; Jessica F. Briffa; Shalem Y. Leemaqz; Rachel A. Burton; Tania Romano; Mary E. Wlodek; Tina Bianco-Miotto (Epigenetics, 2024)
Altered epigenetic mechanisms have been previously reported in growth restricted offspring whose mothers experienced environmental insults during pregnancy in both human and rodent studies. We previously reported changes in the expression of the DNA methyltransferase Dnmt3a and the imprinted genes Cdkn1c (Cyclin-dependent kinase inhibitor 1C) and Kcnq1 (Potassium voltage-gated channel subfamily Q member 1) in the kidney tissue of growth restricted rats whose mothers had uteroplacental insufficiency induced on day 18 of gestation, at both embryonic day 20 (E20) and postnatal day 1 (PN1). To determine the mechanisms responsible for changes in the expression of these imprinted genes, we investigated DNA methylation of KvDMR1, an imprinting control region (ICR) that includes the promoter of the antisense long non-coding RNA Kcnq1ot1 (Kcnq1 opposite strand/antisense transcript 1). Kcnq1ot1 expression decreased by 51% in growth restricted offspring compared to sham at PN1. Interestingly, there was a negative correlation between Kcnq1ot1 and Kcnq1 in the E20 growth restricted group (Spearman’s ρ = 0.014). No correlation was observed between Kcnq1ot1 and Cdkn1c expression in either group at any time point. Additionally, there was a 11.25% decrease in the methylation level at one CpG site within KvDMR1 ICR. This study, together with others in the literature, supports that long non-coding RNAs may mediate changes seen in tissues of growth restricted offspring.